2017
DOI: 10.1136/bmjopen-2017-017296
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a longitudinal study evaluating the impact of rape on women’s health and their use of health services in South Africa

Abstract: IntroductionSouth Africa is a country known for its high levels of HIV infection and sexual violence. Although the interface between gender-based violence, HIV and mental health has been described, there are substantial gaps in knowledge of the medium-term and long-term health impact. The 2010 Global Burden of Disease study excluded many health outcomes associated with rape and other forms of gender-based violence because systematic reviews revealed huge gaps in data and poor evidence of health effects. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…A full account of the Rape Impact Cohort Evaluation (RICE) study methods is presented elsewhere [ 22 ]. The study was conducted within the surrounds of the city of Durban in KwaZulu-Natal (KZN) province, and the RICE clinic was located in a tertiary hospital.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A full account of the Rape Impact Cohort Evaluation (RICE) study methods is presented elsewhere [ 22 ]. The study was conducted within the surrounds of the city of Durban in KwaZulu-Natal (KZN) province, and the RICE clinic was located in a tertiary hospital.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained permission to recruit women from the National and Provincial Prosecuting offices as well as the KZN Provincial Department of Health. Full consent procedures, including written informed consent, are described in the published protocol [ 22 ]. The study team included a trauma counsellor who provided immediate psychosocial support to participants on request, particularly to those who were identified as needing assistance during the study mental health assessments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical approval was granted by the South African Medical Research Council Ethics Committee (Protocol ID-EC019-10/2013). The full study design is reported elsewhere [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Assuming a HIV incidence of 9 and 6% among the rape-exposed and nonexposed groups respectively [ 13 ], and to achieve 90% power to detect a significant difference in HIV incidence, 1008 participants were to be recruited in each cohort. In practice, however, recruiting rape-exposed participants took longer than anticipated resulting in logistical and budgetary constraints.…”
Section: Methodsmentioning
confidence: 99%